PENGARUH PENGENDALIAN INTERN PIUTANG TERHADAP MINIMALISASI PIUTANG TAK TERTAGIH PADA PT. AL IJARAH TAHUN 2014 - Sugeng, Sugeng; Effendi, Syahril; Santoso, Cahyo Budi (Universitas Riau Kepulauan, 2015)
The main activity of the leasing company is financing the procurement of goods, the customer will be paid by installment. Every customer is given the long time limit penyicilannya depending on the agreement with the customer's company. Operating systems such company is certainly not immediately generate cash receipts, but the cause of trade and then later on the day of maturity ocurs cash inflows.Accounts receivable at the company is generally the largest part of current assets as well as the largest part of the total assets of the company. Therefore, control of trade receivables is very important diterapkan.Guna reduce and minimize bad debts. Key words : Internal Control, Bad Debt